IL‐10 promotes homeostatic proliferation of human CD8+ memory T cells and, when produced by CD1c+ DCs, shapes naive CD8+ T‐cell priming. Issue 7 (17th May 2016) - Nizzoli, Giulia; Larghi, Paola; Paroni, Moira; Crosti, Maria Cristina; Moro, Monica; Neddermann, Petra; Caprioli, Flavio; Pagani, Massimiliano; De Francesco, Raffaele; Abrignani, Sergio; Geginat, Jens
Abstract : Role of IL‐10 in human CD8 + T‐cell (CTL) responses: CD1c + DC‐derived IL‐10 fine‐tunes DC maturation, and inhibits selectively the priming and cross‐priming of low‐affinity CTL. In addition, TLR‐stimulated CD1c + DC trans‐present IL‐15, which induces TCR‐independent, "homeostatic" proliferation of memory CTL that is enhanced by IL‐10. Abstract : IL‐10 is an anti‐inflammatory cytokine that inhibits maturation and cytokine production of dendritic cells (DCs). Although mature DCs have the unique capacity to prime CD8 + CTL, IL‐10 can promote CTL responses. To understand these paradoxic findings, we analyzed the role of IL‐10 produced by human APC subsets in T‐cell responses. IL‐10 production was restricted to CD1c + DCs and CD14 + monocytes. Interestingly, it was differentially regulated, since R848 induced IL‐10 in DCs, but inhibited IL‐10 in monocytes. Autocrine IL‐10 had only a weak inhibitory effect on DC maturation, cytokine production, and CTL priming with high‐affinity peptides. Nevertheless, it completely blocked cross‐priming and priming with low‐affinity peptides of a self/tumor‐antigen. IL‐10 also inhibited CD1c + DC‐induced CD4 + T‐cell priming and enhanced Foxp3 induction, but was insufficient to induce T‐cell IL‐10 production. CD1c + DC‐derived IL‐10 had also no effect on DC‐induced secondary expansions of memory CTL. However, IL‐15‐driven, TCR‐independent proliferation of memory CTL was enhanced by IL‐10. We conclude that DC‐derived IL‐10 selects high‐affinity CTL upon priming. Moreover, IL‐10 preserves established CTL memory by enhancing IL‐15‐dependent homeostatic proliferation. These combined effects on CTL priming and memory maintenance provide a plausible mechanism how IL‐10 promotes CTL responses in humans.